2002
DOI: 10.1074/jbc.m111599200
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural 5A Protein of Hepatitis C Virus Modulates Tumor Necrosis Factor α-stimulated Nuclear Factor κB Activation

Abstract: The hepatitis C virus nonstructural protein 5A (NS5A) is a multifunctional phosphoprotein that leads to pleiotropic responses, in part by regulating cell growth and cellular signaling pathways. Here we show that overexpression of NS5A inhibits tumor necrosis factor (TNF)-␣-induced nuclear factor B (NF-B) activation in HEK293 cells, as determined by luciferase reporter gene expression and by electrophoretic mobility shift assay. When overexpressed, NS5A cannot inhibit the recruitment of TNF receptor-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
53
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 59 publications
6
53
0
Order By: Relevance
“…The immunoprecipitates were incubated in kinase reaction buffer (20 mM HEPES, pH 7.4, 1 mM MnCl 2 , 5 mM MgCl 2 , 10 mM ␤-glycerolphosphate, 0.1 mM sodium orthovanadate, 2 mM NaF, and 1 mM dithiothreitol) containing 5 Ci of [␥-32 P]ATP at 30°C for 30 min (38). Substrates used in these kinase reactions were either GST-I B␣ (1 g) containing wild type (amino acids 1-54) or mutant sequences that in residues 32 and 36 were substituted with alanine or Hsp27 (1 g).…”
Section: Methodsmentioning
confidence: 99%
“…The immunoprecipitates were incubated in kinase reaction buffer (20 mM HEPES, pH 7.4, 1 mM MnCl 2 , 5 mM MgCl 2 , 10 mM ␤-glycerolphosphate, 0.1 mM sodium orthovanadate, 2 mM NaF, and 1 mM dithiothreitol) containing 5 Ci of [␥-32 P]ATP at 30°C for 30 min (38). Substrates used in these kinase reactions were either GST-I B␣ (1 g) containing wild type (amino acids 1-54) or mutant sequences that in residues 32 and 36 were substituted with alanine or Hsp27 (1 g).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA corresponding to the NS5B coding sequence of HCV was amplified by PCR using the Korean isolate of HCV (genotype 1b) (11) and subcloned into the BamHI site of pcDNA3 (Invitrogen) or pEF6/Myc-His (Invitrogen). TNFR1, TRADD, TRAF2, MEKK-1, the dominant-negative mutant form of MEKK1 (DN MEKK1), Flag-IKK␣, and Flag-IKK␤ expression vectors were described previously (28,43,44,64). The Flag-IB␣ expression vector was a gift from Dean Ballard (Vanderbilt University).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the phosphorylation pattern of NS5A plays an important role in HCV genome replication (Evans et al, 2004b;Appel et al, 2005). It also interacts with a multitude of cellular proteins and alters the host cells to support viral RNA replication (Gale et al, 1998;Chung et al, 2000;Park et al, 2002;Evans et al, 2004a;Gao et al, 2004).Transposon-mediated insertion mutagenesis (Goryshin & Reznikoff, 1998) is a powerful tool that allows insertion of short peptides into proteins encoded in cloned DNA to evaluate permissive sites in the protein. It can also be used to assess regions of the protein that are dispensable for its functions.…”
mentioning
confidence: 99%
“…The aminoterminal domain of NS5A appears to interact with several cellular proteins (Gale et al, 1998;Chung et al, 2000;Park et al, 2002;Waris et al, 2003;Evans et al, 2004a;Gao et al, 2004) that may be necessary for replication. In addition, an amphipathic a-helix and a zinc-binding site located at the amino terminus are required for replication (Brass et al, 2002; Elazar et al, 2003;Tellinghuisen et al, 2004Tellinghuisen et al, , 2005 et al, 2000) and the carboxyterminal sequences (residues 399-441) have been demonstrated (Zhu et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation